COMPREHENSIVE REHABILITATION OF CHILDREN WITH SENSORY AND INTELLECTUAL DISORDERS - Pakhomova, N.G.; Baranets, I.V.; Lukianenko, A.V.; Leshchii, N.P.; Kachurovska, O.B.; Berezan, O.I.; Olefir, O.I. (World of Medicine and Biology, 2022)
The article presents the results of comprehensive rehabilitation of primary school children with sensory and intellectual disabilities, namely children with sensorineural deafness combined with mild mental retardation. The purpose of the study was to test the effectiveness of a comprehensive, differentiated system of correctional and health work with children of primary school age with complex developmental disorders. This study lasted during 2013–2021, during which a comprehensive rehabilitation of 100 children of primary school age (7–10 years) with severe developmental disabilities, including 53 girls and 47 boys, was carried out. It was found that after a comprehensive corrective and health work in girls of the experimental group of 7–10 years, the repeated indices of the vital index were probably better compared to CG girls of 7–10 years by 4.87 %, strength index – by 3.24 %, Stange's test – by 3.78 seconds, Genchi's test – by 4.69 seconds, Ruffier's test – by 3.26 c.u., Skibinski's index – by 2.32 c.u. At the same time, there was a positive trend in EG boys aged 7–10 years, where recurrent vital signs were probably better than in CG boys aged 7–10 years by 3.00 %, strength index – by 3.97 %, Stange's test – by 6.98 seconds, Genchi's test – by 2.02 seconds, Ruffier's test – by 3.14 c.u., Skibinski's index – by 2.33 c.u. The study's results confirmed their practical significance in the implementation of medical, psychological and pedagogical rehabilitation of this category of children.
Keywords: rehabilitation; physical development; hearing disorders; intellectual disorders; children with complex developmental disorders; correctional and health-improving work